Pengaruh Firm Size, Likuiditas dan Leverage Terhadap Pertumbuhan Laba pada Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia - Erika Agustina; Sri Layla Wahyu Istanti (Jurnal Riset Akuntansi Politala, 2026)
This study aims to examine the effect of firm size, liquidity, and leverage on profit growth in banking companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Profit growth is an important indicator in assessing company performance and business sustainability in the banking sector. This research employs a quantitative approach with purposive sampling, resulting in 10 banking companies as the research sample. The data are analyzed using multiple linear regression with the assistance of SPSS software. The results show that firm size has a negative and significant effect on profit growth, indicating that larger banking companies tend to experience lower profit growth due to increasing operational complexity and potential managerial inefficiencies. Liquidity has a positive but insignificant effect on profit growth, suggesting that a high level of liquidity has not been optimally utilized to generate higher profits. Leverage also shows a positive but insignificant effect on profit growth, indicating that the use of debt has not become a major determinant in increasing profit growth in banking companies. Simultaneously, firm size, liquidity, and leverage explain 23.1% of profit growth, while the remaining percentage is influenced by other factors outside the research model.